Efek Penggunaan Ekstrak Akar Bambu Dan Metabolit Sekunder Trichoderma Harzianum Terhadap Hasil Tanaman dan Intensitas Penyakit Antraknosa Pada Cabai. - Lorenda Alfons; A. Marthin Kalay; Abdul Karim Kilkoda (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2023)
Obstacles that often occur in chili cultivation are low soil fertility and anthracnose attacks caused by fungiColletotrichum capsici. The solution to overcome these two problems is natural ingredients. This research aims to obtain effective concentrations of bamboo root extract (EAB) and secondary metabolites (MS)Trichoderma harzianum to increase yields and reduce the intensity of anthracnose disease in chili plants. The experiment used EAB treatment with concentrations of 0%, 1.0%, 1.5% and 2.0%, and MST. harzianum with concentrations of 0%, 10%, 20% and 30%. The plant responses observed were the number of fruit, fruit weight, fruit length, fruit diameter, and intensity of anthracnose disease. The research results found that the use of EAB and MST. harzianum can increase the yield of chili plants such as the number of fruit, fruit weight and fruit length, and can control anthracnose disease. EAB treatment with a concentration of 2.0% and MST. harzianum with a concentration of 20% is more effective in increasing plant yields and controlling anthracnose disease in chilies. This research is a promising approach in an environmentally friendly and sustainable agricultural system.